Concurrence of aqueous and gas phase contamination of groundwater in the Wattenberg oil and gas field of northern Colorado. (1st January 2016) - Li, Huishu; Son, Ji-Hee; Carlson, Kenneth H.
Abstract: The potential impact of rapid development of unconventional oil and natural gas resources using hydraulic fracturing and horizontal drilling on regional groundwater quality has received significant attention. Major concerns are methane or oil/gas related hydrocarbon (such as TPHs, BTEX including benzene, toluene, ethybenzene and xylene) leaks into the aquifer due to the failure of casing and/or stray gas migration. Previously, we investigated the relationship between oil and gas activity and dissolved methane concentration in a drinking water aquifer with the major finding being the presence of thermogenic methane contamination, but did not find detectable concentrations of TPHs or BTEX. To understand if aqueous and gas phases from the producing formation were transported concurrently to drinking water aquifers without the presence of oil/gas related hydrocarbons, the ionic composition of three water groups was studied: (1) uncontaminated deep confined aquifer, (2) suspected contaminated groundwater - deep confined aquifer containing thermogenic methane, and (3) produced water from nearby oil and gas wells that would represent aqueous phase contaminants. On the basis of quantitative and spatial analysis, we identified that the "thermogenic methane contaminated" groundwater did not have similarities to produced water in terms of ionic character (e.g. Cl/TDS ratio), but rather to the "uncontaminated" groundwater. The analysis indicates that aquifer wells with demonstrated gas phase contamination have not been contacted by an aqueous phase from oil and gas operations according to the methodology we use in this study and the current groundwater quality data from COGCC. However, the research does not prove conclusively that this the case. The results may provide insight on contamination mechanisms since improperly sealed well casing may result in stray gas but not aqueous phase transport. Highlights: Casing failure is the major pathway causing the contamination in Wattenberg field. Contamination include gas phase (methane) and aqueous phase (produced water). Ionic composition of groundwater is key to determine the aqueous phase contaminant. Ionic signatures of THGW were statistically consistent with that of surrounding GW. No significant similarity in ionic characteristics between THGW and PW.